NILAI MORALITAS DALAM LEGENDA MASYARAKAT SUNDA “CIUNG WANARA” VERSI PLEYTE (CWP) “TJARITA TJIOENG WANARA” (PENDEKATAN SEMANTIK) - Gilang Kripsiyadi Praramdana; Aceng Ruhendi Syaifullah; Asep Jejen Jaelani (Jurnal Semantik, 2020)
In this 21st century, the spotlight on character education is a priority research goal, and researchers intend to find character values in one of Ciung Wanara's stories. This research has several specific objectives; 1) Describe the text of the story / fairy story of Ciung Wanara, 2) Interpret the morality values (values) contained in the Ciung Wanara story using a semantic approach. The researcher uses the analytical description method. The element of local wisdom implied in it. the morality values found in Ciung Wanara manuscript are: (1) human morality to God (MMT), which explains in the conversation of 2 (two) storytellers namely nini and balangantrang battery. (Grateful for God's creation) (14%), (2) human morals towards humans (MMS), found there were 5 (five) dominant conversations; a) Aki and Nini balangantrang, b) the conversation of the King and Ciung Wanara, c) the statement and treatment of the Resigned Goddess Naganingrum (71%), then (3) Human morality towards nature (MMA) amounted to 1 (one) treatment figure, namely Ciung Wanara statement regarding the beauty of the forms of two animals namely Ciung (Chicken) and Animal Wanara (Monkey) (14%), after summarizing the morality values contained in the script of the story "Ciung Wanara" predominantly leads to the value of Human Morality against fellow Humans (MMM) as much 71%. while other moral values are not interpreted (non-categories).